Implementasi Sistem Verifikasi Ijazah dan Transkrip pada Jaringan Ethereum Blockchain - Intan Anjali Putri; Aditiya Hermawan; Ardiane Rossi Kurniawan Maranto (Komunitas Dosen Indonesia, 2024)
Blockchain, a decentralized database safeguarded by cryptographic security, has gained prominence for its resistance to manipulation. Its application extends notably to ensuring the security of financial transactions, including the acquisition of digital currencies. This study endeavors to develop a system aimed at validating diplomas and academic transcripts, enhancing their authenticity and bolstering the security of document storage. Leveraging the Ethereum Blockchain and Smart Contracts, the methodology focuses on the utilization of specialized codes executed within the Ethereum network. The outcome of this research manifests as a system blueprint designed for the verification of diplomas and transcripts, integrated within a web-based Ethereum Network platform. By harnessing the Ethereum Blockchain's inherent security features and employing Smart Contracts, the proposed system endeavors to streamline the verification process, ensuring the integrity and reliability of academic credentials while fortifying document storage against potential breaches. Through this innovative approach, the study contributes to advancing the authentication and security standards within the realm of academic documentation management.